Assessing longitudinal profiles of glucocorticoid concentrations in the baleen of male and female southern right whales ( Eubalaena australis) - Ganswindt, Andre (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2024.